AN EMPIRICAL TEST OF COMPETING CORPORATE GOVERNANCE THEORIES ON THE PERFORMANCE OF FIRMS LISTED AT THE NAIROBI SECURITIES EXCHANGE - Aduda, Josiah; Chogii, Ronald; Magutu, Peterson Obara (European Scientific Journal, ESJ, 2013)
The focus of this study was on linking these variables to the contrasting and competing theories of Corporate Governance such as Agency Theory, Stewardship Theory, and Resource Dependence Theory, among others. The role of the Board as a corporate governance tool is widely acknowledged in much of the literature on Corporate Governance. Scholars and practitioners have sought to understand the relationship between various board composition variables and some measure of performance as a means of establishing what the significant board composition variables are and the likely effect of adding or dropping some of these variables in the process of establishing effective boards. This study investigated significance of the board composition variables of size of the board, proportion of outside directors, proportion of inside directors, and the role of CEO duality on firm performance. This study found that the overall regression models for firm performance for both the Return on Assets and Tobin Q ratio are significant. This means that the board composition variables cited above are important predictors of firm performance. The study also found that the significance of the individual variables in the overall specification models have differing significant variables on the basis of the measure of performance selected for the firm. For example, when firm performance is measured by the Return on Assets, the significant variable in the model is the size of the board. Under the Tobin Q ratio firm performance measure, on the other hand, proportion of outside directors is the significant variable. These results imply that under the ROA, there seems to be a dominance of the Resource Dependence Theory while under the Tobin Q ratio, the Agency Theory dominates. The study also found that most surveyed firms tended to favour outside directorships over inside directorships. The prevalence of outside directorships was twice as much as for inside directorships and is in favour of the Agency Theory. The study also found that surveyed firms tended to favour having different persons occupying the two positions of CEO and that of the Chairman of the Board which is in line with the Agency Theory.